2022
DOI: 10.1515/tjb-2022-0093
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models can predict the presence of variants in hemoglobin: artificial neural network-based recognition of human hemoglobin variants by HPLC

Abstract: Objectives This article presents the use of machine learning techniques such as artificial neural networks, K-nearest neighbors (KNN), naive Bayes, and decision trees in the prediction of hemoglobin variants. To the best of our knowledge, this is the first study using machine learning models to predict suspicious cases with HbS or HbD Los Angeles carriers state. Methods We had a dataset of 238 observations, of which 128 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Ucucu et al demonstrated ANN-based recognition of human Hb variants in the HPLC system. The study used clinical samples of known hemoglobinopathies and found that ML was able to detect Hb variants with an accuracy of 99%, specificity of 99%, and sensitivity of 99% [ 61 ]. This implies that an ANN-based ML method has demonstrated high performance and has the potential to be integrated into diagnostic service as a tool for the detection and prediction of hemoglobinopathies.…”
Section: Current Applications Of Ai In Hematologic Cytologymentioning
confidence: 99%
“…Ucucu et al demonstrated ANN-based recognition of human Hb variants in the HPLC system. The study used clinical samples of known hemoglobinopathies and found that ML was able to detect Hb variants with an accuracy of 99%, specificity of 99%, and sensitivity of 99% [ 61 ]. This implies that an ANN-based ML method has demonstrated high performance and has the potential to be integrated into diagnostic service as a tool for the detection and prediction of hemoglobinopathies.…”
Section: Current Applications Of Ai In Hematologic Cytologymentioning
confidence: 99%